Distribution of Home Renovation Assistance in Gampong Buket Drien, Sungai Raya Padang District - Abdillah, Alwin; Zulfikar; Syakira (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2022)
This research tells the story of the Distribution of Assistance for Rehab Houses in Buket Drien Village in a Review of the Siyasah Principles and Regulation of the Minister of Social Affairs No. 20 of 2017. From the data collection that the author has obtained, the author is of the opinion that the distribution of assistance for rehabilitation of uninhabitable houses is still not going well, there are still obstacles that make beneficiary communities feel annoyed because of delays in distribution to some beneficiaries. This research is classified as a field study with a qualitative approach. The methodology used is a case study and phenomenological study. The research results conclude that; The distribution stage implemented by Buket Drien village went through 3 stages, namely the data collection stage, the verification stage, and the distribution stage. When viewed from the political underpinnings of Islam or the siyasa principle, especially on the principle of justice, the writer can conclude that the implementation of the principle of justice at the distribution stage in the implementation of assistance for renovating uninhabitable houses is not yet good.